Alterations to influenza virus hemagglutinin cytoplasmic tail modulate virus infectivity. - Simpson, D A (1992)
The influenza virus hemagglutinin (HA) contains a cytoplasmic domain that consists of 10 to 11 amino acids, of which five residues have sequence identity for 10 of 13 HA subtypes. To investigate properties of these conserved residues, oligonucleotide-directed mutagenesis was performed, using an HA cDNA of influenza virus A/Udorn/72 (H3N2) to substitute the conserved cysteine residues with other residues, to delete the three C-terminal conserved residues, or to remove the entire cytoplasmic domain. The altered HAs were expressed in eukaryotic cells, and the rates of intracellular transport were examined. It was found that substitution of either conserved cysteine residue within the cytoplasmic domain did not affect the rate of intracellular transport, whereas deletion of residues within the C-terminal domain resulted in delayed cell surface expression. All the altered HAs were biologically active in hemadsorption and fusion assays. To investigate whether the wild-type HA and HAs with altered cytoplasmic tails could complement the influenza virus temperature-sensitive transport-defective HA mutant A/WSN/33 ts61S, the HA cDNAs were expressed by using a transient expression system and released virus was assayed by plaque analysis. The wild-type HA expression resulted in a release of approximately 10(3) PFU of virus per ml. Antibody neutralization of complemented virus indicated that the infectivity was due to incorporation of wild-type H3 HA into ts61S virions. Sucrose density gradient analysis of released virions showed that each of the HA cytoplasmic domain mutants was incorporated into virus particles. Virions containing HAs with substitution of the cysteine residues in the cytoplasmic domain were found to be infectious. However, no infectivity could be detected from virions containing HAs that had deletions in their cytoplasmic domains. Possible roles of the HA cytoplasmic domain in forming protein-protein interactions in virions and their involvement in the initiation of the infection process in cells are discussed.